Local production of 17β-oestradiol in the endometrium during the implantation window: a pilot study - L B P M Stevens Brentjens; D Obukhova; B Delvoux; J E den Hartog; B N Bui; F Mol; J P de Bruin; D Besselink; G Teklenburg; F Morgan; M Baker; F J M Broekmans; et al. (Bioscientifica, 2023)
Sex steroids are converted to bioactive metabolites and vice versa by endometrial steroid-metabolising enzymes. Studies indicate that alterations in this metabolism might affect endometrial receptivity. This pilot study determined whether the endometrial formation and inactivation of 17β-oestradiol differed between the supposedly embryo-receptive endometrium and non-receptive endometrium of women undergoing IVF/intracytoplasmic sperm injection (ICSI). Endometrial biopsies were obtained from IVF/ICSI patients 5-8 days after ovulation in a natural cycle, prior to their second IVF/ICSI cycle with fresh embryo transfer (ET). Endometrial biopsies from patients who achieved clinical pregnancy after fresh ET (n = 15) were compared with endometrial biopsies from patients that did not conceive after fresh ET (n = 15). Formation of 17β-oestradiol (oxidative 17β-hydroxysteroid dehydrogenases (HSDs)), oestrone (reductive HSD17Bs) and inhibition of HSD17B1 activity were determined by high-performance liquid chromatography. The endometrial transcriptome was profiled using RNA sequencing followed by principal component analysis and differentially expressed gene analysis. The false discovery rate-adjusted P < 0.05 and log fold change >0.5 were selected as the screening threshold. Formation and inactivation of 17β-oestradiol resulted similar between groups. Inhibition of HSD17B1 activity was significantly higher in the non-pregnant group when only primary infertile women (n = 12) were considered (27.1%, n = 5 vs 16.2%, n = 7, P = 0.04). Gene expression analysis confirmed the presence of HSD17B1 (encoding HSD17B1), HSD17B2 (encoding HSD17B2) and 33 of 46 analysed steroid metabolising enzymes in the endometrium. In the primary infertile subgroup (n = 10) 12 DEGs were found including LINC02349 which has been linked to implantation. However, the exact relationship between steroid-metabolising enzyme activity, expression and implantation outcome requires further investigation in larger, well-defined patient groups.